Local Governance in Accelerating SDGs Achievement in Riau, Indonesia - Rodi Wahyudi; Rony Jaya; Devi Deswimar; Zikri Darussamin (UIN Sunan Gunung Djati, 2024)
Encouraging more effective governance is needed to accelerate the 2030 SDGs agenda both on a global, national, and local scale. The purpose of writing this article is to analyze and evaluate local governance in accelerating the achievement of SDGs on a local scale at the provincial government level, especially in Riau, Indonesia. The method uses a qualitative approach by analyzing various documents related to SDGs on a global, national, and local scale, especially in Riau province, with in-depth research through interviews and literature studies. The study results show that local governance has not been effective in accelerating the achievement of SDGs in Riau. The Riau provincial government is quite committed to the SDGs agenda, but its capacity and policy initiatives are still minimal and limited. The preparation and implementation of regional action plans for the SDGs have not been optimally integrated and coordinated, especially regarding inclusivity and involvement of non-governmental actors.